Psychological Essentialism at the Explicit and Implicit Levels: The Unique Status of Social Categories1. (5th March 2019) - Karasawa, Minoru; Asai, Nobuko; Hioki, Koichi
Abstract: Psychological essentialism refers to a naive theory concerning fundamental elements that bring a category into its existence. The present study examined the structure of this lay theory as well as its implicitness, with a special focus on social categories. In Study 1, Japanese college students rated a number of categories that were natural‐kind, social, or human artifacts, in terms of different elements of essentialist beliefs. A factor analysis revealed that entitativity and naturalness are the common underlying dimensions across these category domains. We also identified some natural‐kind and human artifact categories that can be used as two extreme referent points for the examination of naturalness perceived in a whole array of social categories. Study 2 assessed implicit and automatic judgments on naturalness using a go/no‐go task, and compared them to explicit judgments. Unlike natural kinds and artifacts, social categories were essentialized to a greater extent at the implicit level. These results suggest a dual process of intuitive and deliberate cognition, particularly involving social categories, with implications concerning the bases of stereotypes and prejudices.